The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1108/eb018579
|View full text |Cite
|
Sign up to set email alerts
|

Materiality and Risk Judgements: A Review of Users' Expectations

Abstract: In reviewing contemporary literature on materiality judgement and the audit expectations gap (AEG), this paper considers an apparent void concerning that aspect of the AEG caused by the non‐disclosure of materiality and risk thresholds and criteria in the financial reports. The review enables the formation and discussion of two premises: first, disclosing cornerstone concepts, such as materiality and risk judgements, in financial reports enhances users' understanding of the limitations of information contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…13. De Martinis and Burrowes (1996) argue that there is an inverse relationship between materiality thresholds and another type of risk-audit risk. Chong and Vinten (1996) similarly proposes an audit risk model in which materiality thresholds may vary with audit risk.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…13. De Martinis and Burrowes (1996) argue that there is an inverse relationship between materiality thresholds and another type of risk-audit risk. Chong and Vinten (1996) similarly proposes an audit risk model in which materiality thresholds may vary with audit risk.…”
Section: Resultsmentioning
confidence: 98%
“…In the UK no guidelines have been issued. In Australia, New Zealand, Canada, Fiji, and South Africa (De Martinis & Burrowes, 1996) the standards give more guidance than in the UK and USA although the guidelines are not very specific. Australian accounting standards AAS 5 and AASB 1031 provide a range of 5% to 10% of an appropriate base as a guideline for materiality thresholds, with below 5% being immaterial and above 10% material.…”
Section: Introductionmentioning
confidence: 94%
“…There is some evidence that the disclosure of materiality thresholds might enhance users’ understanding of an audit, i.e. perceptions of audit quality (Jennings, Kneer & Reckers, , ; De Martinis & Burrowes, ). Experimental market studies (Fisher, ; Tuttle, Coller & Plumlee, ; Davis, ) have shown that disclosure of materiality improves investor perceptions and leads to greater market efficiency.…”
Section: Prior Research and Research Questionsmentioning
confidence: 99%
“…In summary, they document that internal company error is the primary cause to which company disclosures attribute restatements, although a significant portion of restatements are attributed to accounting standards. Some countries do have professional guidance on materiality including Australia, Canada and South Africa (De Martinis and Burrowes, 1996), but even in these countries the disclosure of materiality thresholds and criteria in the financial reports is not required. The non-disclosure of these concepts, and lack of explanation regarding what, and why information is disclosed makes such reports less understandable and less useful for users' decision making (De Martinis and Burrowes, 1996).…”
Section: Maj 266mentioning
confidence: 99%